Presentation of a Structural Model for Assessing Supply Chain Capabilities in the Iranian Food Industry - Maryam Arbab Nooshabadi,; Ghodrati Ghazaani, Hassan; Jabbari, Hossein; Farzinfar, Ali Akbar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of this research was to investigate the supply chain capabilities in the food industries by using indicators of competitive advantage, financial performance, and shareholder value to improve supply chain capabilities and ultimately design an appropriate structural model.Methodology:  The present study is quantitative and descriptive-analytical in nature. The population of the study includes employees and experts in the food manufacturing industries, totaling 500 individuals. To determine the minimum sample size required, Morgan's table for limited populations was used, and ultimately, 217 completed questionnaires were returned and analyzed. The data collection tool was a researcher-made questionnaire. Data analysis was performed using structural equations and AMOS software.Findings: The results indicated significant relationships and components of the presented model. Factor analysis results showed that the paths and causal relationships between external and internal constructs in the structural model were confirmed with 95 percent probability.Conclusion: In general, initiatives based on cost reduction and productivity improvement are easier than others. For example, if an initiative focusing on reducing inventory levels leads to achieving previous sales levels, the benefits of this initiative are easily measurable. However, long-term growth requires an increase in revenue, and managers need to focus on all four methods mentioned above to enhance company value.